A Review of Opportunistic Infections in Modern Immunosuppressed Populations - AL-Sadoon, Maysaloun; Sabbar, Ban Anas (Libyan Journal of Medical and Applied Sciences, 2026)
Opportunistic infections are a major clinical concern in individuals with impaired immune systems. More widespread organ transplantation, chemotherapy, biologic therapies and long-term corticosteroids had created a population at greater risk of such infections. Consequently, a variety of patients including not only those with late-stage HIV infection have been affected by opportunistic pathogens. The type and degree of immune deficiency affect the range of potential infections. Neutropenia, for example, is known to come with severe bacterial and invasive fungal infection; defects in T-cell immunity led to increased susceptibility to viral reactivation and infections by intracellular pathogens. Early recognition and application of appropriate diagnostic strategies are key to maximizing patient outcomes. New diagnostic tools, including molecular tests and metagenomic sequencing have enhanced pathogen diagnosis in the immunocompromised. Successful management requires early initiation of antimicrobial therapy, targeted adjustment of immunosuppression and supportive clinical care. Other critical preventive strategies include vaccination, antimicrobial prophylactic measures, screening for latent infections and establishing infection-control practices. This review describes the common pathogens, risk factors, diagnostic approaches and preventive measures relevant to opportunistic infections in modern immunocompromised populations.